PERSEPSI AKADEMISI DAN PRAKTISI AKUNTANSI TERHADAP AKUNTANSI FORENSIK SEBAGAI PROFESI INDONESIA - Adhysti Kartika Zamira; Darsono Darsono (Diponegoro Journal of Accounting, 2014)
This research aims to analyze the difference between academic and practitioner perceptions regarding forensic accounting as a profession in Indonesia on the issues of theory and intellectual technique, relevance, training period, motivation, autonomy, commitment, sense of community and the code of ethics. The object research was academics and practitioners in Semarang City.This research used purposive sampling technique in data collection. Data was obtained by distributing 100 questionnaires in state university and government institution such as BPK and BPKP in Semarang. 66 respondents (66%) that consist of 31 academics and 35 practitioners give their responses. Data was analyzed by Independent Sample T Test by SPSS version 22 software package.The result of this research shows that there is no significant difference in the perception between academics with practitioner in theory and intellectual technique, relevance, training period, motivation, autonomy, and the code of ethics. The result of this research shows that there is a significant difference in the perception between academics with practitioner in commitment and sense of community. Moreover, the overall respondents give a positive perception to the eighth research variables which means that according to the respondents, forensic accounting met the eighth criteria that distinguish the occupation and profession according to Pavalko’s criteria.